In House Training: Peningkatan Kemampuan Guru dalam Menerapkan Authentic Assesment Pembelajaran - Sobri Sobri; Tatu Hilaliyah; Ilmi Solihat; Imam Safi'i; Subali Subali (Universitas Mathla'ul Anwar Banten, 2022)
IN HOUSE TRAINING: IMPROVING TEACHER ABILITY IN APPLYING AUTHENTIC ASSESSMENT OF LEARNING: Authentic assessment is a form of assessment that can measure students' abilities holistically, but not all teachers at SDN Gerem 1 Cilegon City are able to develop it. Therefore, it is necessary to strive. One of them is through intensive training activities. This article aims to describe the activities of the partnership program to the community in the form of authentic assessment training in learning at the Gerem 1 Elementary School in Cilegon City. The procedure used in this activity consists of three stages, namely the preparation stage of the training equipment, the implementation of the training, and the reflection stage. The training activities that have been carried out can improve the competence of teachers in carrying out various forms of authentic assessment.